Features force between the foot and performance of special-based tests young basketball players - Stroganov, S. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Purpose. A quantitative analysis of biomechanical force interactions between the foot and the support when the athletes special tests.